Ambient ozone pollution and prevalence of chronic kidney disease: A nationwide study based on the China National survey of chronic kidney disease. (November 2022) - Yang, Chao; Wang, Wanzhou; Wang, Yueyao; Liang, Ze; Zhang, Feifei; Chen, Rui; Liang, Chenyu; Wang, Fulin; Li, Pengfei; Ma, Lin; Li, Shuangcheng; Deng, Furong; et al.
Abstract: The health hazards of ambient ozone (O3 ) pollution are receiving increasing attention worldwide. However, the evidence on the association between O3 and risks of chronic kidney disease (CKD) remains insufficient and inconsistent, particularly in developing countries where there is an absence of macroscopic investigations at a large population scale. Based on data from a representative nationwide cross-sectional CKD survey in 13 Chinese provinces and a high resolution O3 air pollution inversion dataset, generalized linear models were used to evaluate the associations of O3 concentration with prevalence of CKD. The results of this study suggested that long-term O3 exposure was positively associated with the risk of CKD. A 10 μg/m 3 increment in O3 concentration was associated with an increased odds of CKD prevalence [OR = 1.11 (95% CI: 1.03, 1.21)] among all the 47, 086 participants. Stronger associations were found in urban regions, younger adults <65 years, and people with higher socio-economic status (income and education level). A 10 μg/m 3 increment in O3 concentration was associated with a higher increased odds of CKD prevalence in urban regions [OR = 1.31 (95% CI: 1.16, 1.47)] compared to rural regions [OR = 0.95 (95% CI: 0.84, 1.08), P for subgroup difference<0.001]. A stronger association of O3 concentration with CKD prevalence was found among younger people aged <65 years [OR = 1.21 (95% CI: 1.10, 1.33)] compared to those aged ≥65 years [OR = 0.92 (95% CI: 0.79, 1.07), P for subgroup difference = 0.003]. Our study demonstrated that long-term O3 exposure may increase risk of CKD in the general Chinese population, and the findings stressed the importance of persistent efforts in air pollution prevention and control. Graphical abstract: Image 1 Highlights: The first nationwide study to evaluate the association between O3 and CKD in China. O3 air pollution was positively associated with odds of CKD prevalence. Stronger associations were found in urban regions. Stronger associations in young adults and people with high socio-economic status.